The effect of corporate social responsibility on brand image and brand equity and its impact on consumer satisfaction - Joana Araújo; Inês Veiga Pereira; José Duarte Santos (Administrative Sciences, 2023)
This paper aims to study the effect of corporate social responsibility (CSR) on brand image and brand equity and its impact on consumer satisfaction. The study follows a quantitative methodology, using the implementation of an online questionnaire distributed to people who bought, during the pandemic, a product that used a CSR action. Subsequently, data were analyzed through Smart PLS, following the Structural Equation Model. It was possible to conclude that the CSR initiatives positively affect consumer satisfaction through the mediating effect of brand image and brand equity. Further, brand image and brand equity improve when companies use CSR initiatives, and, despite what previous research has concluded, consumer satisfaction is not affected directly when CSR initiatives are used. This research has also showed that CSR's impact on brand image is higher for men, and CSR initiatives' impact on brand equity is also higher for regular purchase consumers.
Keywords: 350; brand equity; brand image; consumer satisfaction; corporate social responsibility